Synthesis and characterisation of tetrabutylammonium bromide-based deep eutectic solvents for DNA solvation - Yusof, Rizana (2016)
Conventionally, DNA is stored in aqueous solution under refrigeration for short and long-term storage. However, slow hydrolytic can disrupt the DNA helical structure and result for a searching of new medium in which DNA is stable for long periods at room temperature. Twenty of new tetrabutylammonium bromide (TBABr)-based DESs were successfully synthesised using various hydrogen bond donors (HBDs) (ethylene glycol, 1,3-propanediol, 1,5-pentanediol and glycerol) with different ratios. Nuclear magnetic resonance (NMR) and Fourier-transform infrared spectroscopy (FTIR) analyses were carried out to identify the molecular structures of the DESs. The properties of the DESs were affected by the structures and ratio of HBD and temperatures. When the length of the HBD decreased, the DESs became less viscous, more conductive and denser. Upon heating, density and viscosity of the DESs decreased while ionic conductivity increased. The molecular properties for one of the DESs, tetrabutylammonium bromide: ethylene glycol (TBABr:EG) were studied by molecular dynamic (MD) simulation. A good agreement for the DESs densities from experimental and simulation data with a small difference (less than ±3.91%) have validated the force fields and proved the accuracy of the simulation systems. When the ratio of ethylene glycol (EG) increased, the self-diffusion coefficient of ions also increased, resulting in the TBA+ cations moving further away from Br- anions. The attraction of the Br- anions to the EG molecules led to formation of hydrogen bonds which were confirmed by radial distribution function (RDF) and FTIR analysis. The calf thymus DNA was analysed biophysically in the DESs that were previously characterised using various spectroscopic methods. The electrostatic attractions and hydrophobic interactions were evidenced between TBA+ cations and DNA. The DESs groove bound via hydrogen bonding into the DNA minor groove, which confirmed through the ability of DES to displace 4',6-diamidino-2-phenylindole (DAPI) with Stern-Volmer constants (Ksv) in range of 91.08 to 100.15 M-1. A combination of electrostatic, polar and hydrophobic interactions between the DES and DNA has contributed to the DNA stability. The strong binding of the DESs to DNA was obtained as the length of HBD decreased and the ratio and polarity of the HBD increased. Hence, TBABr:EG (ratio 1:5) showed the highest binding constant (Kb) of 5.75 x 105 M-1 with the lowest Gibbs free energy (ΔGo) of -32.86 kJmol-1. The DESs maintained the B-DNA conformation at 25°C in concentration of 25% in all the DESs, except 50% for TBABr:1,3-PD. The DESs stabilised the DNA helical by melting at 44 to 50°C, which was 1 to 7°C higher than water. TBABr:EG was able to store DNA for 2 months and TBABr:1,3-PD, TBABr:1,5-PD and TBABr:Gly for up to 6 months. The DESs with HBDs more than 3 carbons exhibited long term-stability, as they were more effective in reducing DNA denaturation. The presence of various interactions between the DESs and DNA were responsible for the long-term stability of the DNA in the DESs. Hence, the results revealed that the DNA was better solvated in DESs rather than aqueous solution.